Synchrotron-based X-ray absorption spectroscopy for art conservation: looking back and looking forward - Cotte, Marine; Susini, Jean; Dik, Joris; Janssens, Koen (Accounts of chemical research, 2010)
A variety of analytical techniques augmented by the use of synchrotron radiation (SR), such as X-ray fluorescence (SR-XRF) and X-ray diffraction (SR-XRD), are now readily available, and they differ little, conceptually, from their common laboratory counterparts. Because of numerous advantages afforded by SR-based techniques over benchtop versions, however, SR methods have become popular with archaeologists, art historians, curators, and other researchers in the field of cultural heritage (CH). Although the CH community now commonly uses both SR-XRF and SR-XRD, the use of synchrotron-based X-ray absorption spectroscopy (SR-XAS) techniques remains marginal, mostly because CH specialists rarely interact with SR physicists. In this Account, we examine the basic principles and capabilities of XAS techniques in art preservation. XAS techniques offer a combination of features particularly well-suited for the chemical analysis of works of art. The methods are noninvasive, have low detection limits, afford high lateral resolution, and provide exceptional chemical sensitivity. These characteristics are highly desirable for the chemical characterization of precious, heterogeneous, and complex materials. In particular, the chemical mapping capability, with high spatial resolution that provides information about local composition and chemical states, even for trace elements, is a unique asset. The chemistry involved in both the object's history (that is, during fabrication) and future (that is, during preservation and restoration treatments) can be addressed by XAS. On the one hand, many studies seek to explain optical effects occurring in historical glasses or ceramics by probing the molecular environment of relevant chromophores. Hence, XAS can provide insight into craft skills that were mastered years, decades, or centuries ago but were lost over the course of time. On the other hand, XAS can also be used to characterize unwanted reactions, which are then considered alteration phenomena and can dramatically alter the object's original visual properties. In such cases, the bulk elemental composition is usually unchanged. Hence, monitoring oxidation state (or, more generally, other chemical modifications) can be of great importance. Recent applications of XAS in art conservation are reviewed and new trends are discussed, highlighting the value (and future possibilities) of XAS, which remains, given its potential, underutilized in the CH community.